Protists modulate fungal community assembly in paddy soils across climatic zones at the continental scale. (September 2021) - Huang, Xing; Wang, Jianjun; Dumack, Kenneth; Liu, Weiping; Zhang, Qichun; He, Yan; Di, Hongjie; Bonkowski, Michael; Xu, Jianming; Li, Yong
Abstract: Soil fungi have important functions in agricultural ecosystems. They promote crop growth by driving soil nutrient cycling and by forming mycorrhizal symbioses with crop species. Most studies on soil fungi have focused on detecting the edaphic factors that structure fungal communities, but little is known about how climate influences the soil microbiome. Moreover, a profound understanding of how soil fungal communities are modulated by other soil organisms, such as protist predators, is lacking. We investigated the spatial succession of fungal assemblages in China and their potential predator-prey relationships with protists across four climatic zones using 18S rDNA amplicon sequencing. Although stochastic processes dominated the assembly of fungal communities, deterministic drivers of community assembly were more important in high-latitude climatic zones (that is, in the temperate and continental zones) than in low-latitude climatic zones (that is, in the tropics and subtropics). Random forest and variation partitioning analyses showed that biotic effects influenced fungal communities as much as abiotic effects. Biotic factors were better predictors of the abundance of several saprophytic and mycorrhizal fungi than abiotic factors. This finding was further supported by a network analysis, which indicated that the intensity of fungi-protist interactions may stimulate the divergence of prey fungal communities. Our results reveal for the first time the nonnegligible effects of biotic factors on soil fungal community assembly across substantially different climatic zones. The biological mechanisms underlying these effects can be well understood within a predator-prey relationship framework in which protists exert strong top-down control on fungal communities. Highlights: Stochasticity dominates fungal assembly in paddy soil. The importance of deterministic process in fungal assembly increases with latitude. Both biotic and abiotic factors affected the spatial variation of fungal communities. Protists are important biotic factors on shaping fungal communities.